TEACHERS’ PERCEPTIONS REGARDING ENGLISH LANGUAGE PROFICIENCY AND TEACHING EFFECTIVENESS - Syifa Aisyah (Institut Pendidikan Indonesia Garut, 2022)
Most English teachers teach students that the discussions to be taught are not so detailed that most students do not fully understand what the teacher is teaching. There are also teachers who give only assignments at the beginning of the lesson without explained the material that will be taught beforehand. So many students are overwhelmed and don't understand learning. In this situation, the study finds out how teachers feel about English language proficiency and their teaching effectiveness in English lessons. The study used a qualitative approach with semi-structured interview. The study was conducted at one of the Junior High School in Garut, West Java. It collected data from a Junior High School teachers. Furthermore, the study found that the relationship between English language proficiency and teaching effectiveness is that if a teacher had mastered English correctly and if a teacher had applied the right way of learning, especially in English study will be certainly improve student skills. The teacher will be very easy to present to the children and will make effective teaching in the classroom.